Relations between the European Union and the Andean Community of Nations free trade agreements - Quispe-Remón, Florabel (Iberoamerican Journal of Development Studies, 2020)
In the article, it is addressed the origin and evolution of the Andean Community of Nations (ACN) and its relationship with the European Union (EU). The initial relationship of cooperation through the system of generalized preference of the EU towards the ACN and the subsequent intention of both organizations to reach an agreement of the Association that includes, in addition to cooperation, the commercial and political spheres is analyzed. After the failure of this attempt of Association Agreement between both blocks, the EU initiated negotiations with the Member States of the ACN independently, which were concluded with the signing of the Commercial Agreement by three States of the four members of the ACN. This aspect is analyzed, besides visualizing the statu quo of the relationship and the repercussion of the commercial agreements on the member countries of the ACN and for the ACN itself.